2019
DOI: 10.1037/lhb0000308
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 21-item short form of the Attitudes to Sexual Offenders (ATS) Scale.

Abstract: The Attitudes to Sexual Offenders scale (ATS; Hogue, 1993) is one of the most widely-used measurement instruments for assessing views about sexual offenders. The ATS has been used in a variety of contexts, most commonly in comparing forensic professionals and non-professionals in relation to their views about this population. This paper offers a review of the methods used to examine attitudes toward sexual offenders currently available, before systematically outlining the validation of a 21-item shortened vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…In this study, we explore attitudinal differences towards individuals with sexual convictions among undergraduate students and professionals who work with this population. However, our focus is not simply on describing the same differences that have been reported in previous reviews Hogue & Harper, 2019). Instead, we investigate the effects of attitudes on risk judgments made by these groups in relation to hypothetical perpetrators of sexual offenses.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, we explore attitudinal differences towards individuals with sexual convictions among undergraduate students and professionals who work with this population. However, our focus is not simply on describing the same differences that have been reported in previous reviews Hogue & Harper, 2019). Instead, we investigate the effects of attitudes on risk judgments made by these groups in relation to hypothetical perpetrators of sexual offenses.…”
Section: Introductionmentioning
confidence: 91%
“…One limitation of this research was the use of explicit self-report measures to assess the sensitive and politically charged topic of attitudes towards sexual offenders which could lead to socially desirable responding . However, recently published data from Hogue and Harper (2019) found that ATS-21 scores were uncorrelated to scores on a social desirability scale, suggesting that the ATS-21 can provide an accurate insight into individuals' attitudes towards sexual offenders. Future research could look to replicate our findings using indirect measures of attitudes, such as a single-target implicit association test (IAT).…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…measure (Hogue & Harper, 2019) to establish their baseline levels of attitudes towards people convicted of sexual offenses. While this may not appear to be directly relevant to the current investigation, it has been found that people typically report completing the ATS-21 with 'pedophiles' and/or 'rapists' in mind .…”
Section: Attitudes To Sex Offenders Scale (Ats-21) Participants Compmentioning
confidence: 99%
“…As we could link demographic data using Prolific IDs collected in phase one, these data were not requested again here. We also did not ask participants to complete the ATS-21 again, as scores on this measure have been reported to be stable over time and resistant to individual experimental influence (Hogue & Harper, 2019). We asked participants to complete the SPS measure, followed by the same ST-IAT as was used in phase one.…”
Section: Procedures -Phasementioning
confidence: 99%
“…The intervention evidences the value in taking a narrative approach to working with staff to understand their attitudes and perceptions towards MSO, rather than delivering traditional training, which has been found to have little effect in increasing positive attitudes. 19 The intervention has one major limitation that would require revisions if it were to be delivered again. As the researcher designed, delivered and evaluated the workshop, there is potential for researcher bias to have been present.…”
Section: Strengths and Limitationsmentioning
confidence: 99%